Caracterização da diversidade e potencial catabólico de bactérias isoladas de aquífero contaminado com creosoto para formação de um consórcio de bactérias degradadoras desse composto - Francisco Singulani Castanon (2018)
Creosote is a complex mixture of chemical constituents comprising diverse chemical structures, especially polycyclic aromatic hydrocarbons (PAH). Due to the potential toxicity, carcinogenicity and mutagenicity of many of its compounds, creosote waste sites represent a threat to the environment and the removal of these compounds from contaminated soil and groundwater is essential. For this purpose, the biological treatment is considered an efficient and financially affordable choice. This study aimed to evaluate the bacteria diversity in aquifers contaminated with creosote, the potential for creosote degradation and production of surface active compounds of these isolates and to select creosote degrading bacteria consortium for application in bioremediation processes. Contaminated aquifer samples were collected from eight wells identified as PP20 (1), PP206 (2), PP207 (3), PM208 (4), PM211 (5), PP29 (6), PP203 (7), and PP223 (8). These sampling points were characterized for total bacterial and degrading bacteria. The average density of total heterotrophic bacteria was 1.78 x 107 NMP/g and the naphthalene, anthracene and phenol degrading bacteria were 4.64 × 106, 2.44 × 106, 8.26 × 106 NMP/g respectively, in the aquifer wells. 77 bacteria were isolated and identified by the enrichment technique using creosote (1% v / v) as the sole source of carbon. The observed genus were Pseudomonas, Enterobacter, Serratia, Stenotrophomonas, Bacillus, Comamonas, Enterococcus, Citrobacter, Pseudochrobactrum, Delftia, Rhizobium, Sphingobacterium, Kosakonia e Alcaligenes, with predominance of the genus Pseudomonas. During the enrichment, the DGGE technique was used to monitor the change in community structure every week, besides observing changes in the abundance of each group during the experiment. Isolates were evaluated by gas chromatography coupled to mass spectrometry for their creosote degradation potential (0.25%) in BHB medium supplemented with yeast extract (0.2%). Enterobacter sp. M3P8/2 (33.71%), Enterobacter sp. M3P8/1 (33.60%), Alcaligenes sp. B/4 (33.55%) e Bacillus cereus T9P9/3 (33.42%) obtained the highest values of degradation. Isolates were also evaluated for the ability to produce surface active compounds in BHB medium supplemented with yeast extract (0.02%) and creosote (1%). Regarding the surface tension, 31.2% of the isolates reduced to values below 45 mN/m and for emulsifying activity, 18.2% of the isolates reached values above 55%. The Pseudomonas putida group T9P4/2 bioemulsifier was characterized as a lipopeptide. The six isolates that obtained the highest percentages of creosote degradation in aquifer samples (Pseudomonas sp. R106-4, Pseudomonas putida group R206-6, Achromobacter sp. R108(10-5), Stenotrophomonas sp. R301-5, Pseudomonas putida group T9P6/1 e Alcaligenes sp. B/4) were chosen to form a consortium, which was used in a complete 24 factorial design, varying the conditions of presence of the autochthonous microbiota, aeration, nutrients and the consortium, to simulate the biostimulation and/or bioaumentation techniques in microcosms with aquifer samples. In this experiment, up to 86% of creosote degradation was observed in one of the treatments, being the presence of consortium, autochthonous microorganisms and aeration considered as significant factors during the process. These data show that the consortium formed is effective in creosote degradation in aquifer samples and this information will be useful for future in situ bioremediation of creosote contaminated aquifers.